New genus and two new species of the family Ethmolaimidae (Nematoda: Chromadorida), found in two different cold-seep environments - Nara, Bezerra Tania; Ellen, Pape; Freija, Hauquier; Ann, Vanreusel; Jeroen, Ingels (Zootaxa, 2013)
This study describes a new genus Dystomanema gen. nov. with two new species, D. cadizensis sp. nov. and D. brandtae sp. nov. within the family Ethmolaimidae, subfamily Neotonchinae, based on specimens from two low-activity cold-seep environments at distant geographical locations. The new genus was first identified in samples from the Darwin mud volcano (1100m depth) in the Gulf of Cádiz and later on also found in samples from a low-activity seep in the Larsen B embayment (820m depth) off the eastern Antarctic Peninsula. Until now, the family Ethmolaimidae contained nine genera: Ethmolaimus and Paraethmolaimus in the subfamily Ethmolaiminae, and Comesa, Filitonchoides, Filitonchus, Gomphionchus, Gomphionema, Nannolaimus, and Neothonchus in the subfamily Neotonchinae. The most important family characteristics are: an annulated cuticle bearing transverse rows of dots, cephalic sensilla arrangement of 6+6+4, a spiral amphid, an oesophagus with muscular posterior bulb, paired gonads and males with cup-shaped precloacal supplements. The new genus resembles Comesa and Neotonchus, but is typified by a ventrally displaced oral opening with three very small teeth that are easily overlooked. D. cadizensis gen. nov. sp. nov. is characterized by the 1401-2123µm long body; cuticle transversally striated with fine punctation; head conical; low lips; amphid spiralled 3 turns, oral opening ventrally displaced, male with outstretched testes; spicules of equal size; gubernaculum plate-like and ten to twelve conspicuous cup-shaped precloacal supplements with external longitudinal articulated flange. D. brandtae gen. nov. sp. nov. can be distinguished by the 2438-3280µm long body; cuticle transversally striated with fine punctuation; head conical; low lips; amphid spiraled 3+ turns; oral opening ventrally displaced; male with anterior testes outstretched and posterior one smaller and reflexed; spicules of equal size; gubernaculum plate-like and twenty conspicuous cup-shaped precloacal supplements with external longitudinal articulated flange. Notes on the ecology and habitat of the new genus are provided in light of its discovery in cold-seep environments.